Correlation and regression analaysis for some economic characteristics of tobacco genotypes (Nicotiana tabacum L.) - صوفان, قمر; بولص خوري; نزار معلا (Latakia University Journal -Biological Sciences Series, 2024)
The experiment was carried out in a nursery at the Faculty of Agricultural engineering. Tishreen University- Lattakia- Syria. during the two agricultural seasons 2021 and 2022. by the cultivation of three Tobacco genotypes (Prilep- Basma- Baladi). Half diallel cross was made between different genotypes of tobacco. In The following season, an evaluation of the genotypes was performed that were distributed according to the Randomized Complete Block Design (R.C.B.D) with three replicates per treatment. The correlation relationships between: Dry Weight of Leaves (DWL), Fresh Weight of Leaves (FWL), Specific Leaf Weight, Plant Leaf Area, DWL/FWL ratio were studied in order to determine the traits that can be adopted as selection criteria for improving the Dry Weight of Leaves. The results show the strongest desirable and significant correlation of the dry weight of leaves was with the fresh weight of leaves (r = 0.9), and fresh weight of leaves with specific leaf weight (r = 0.9), while the second strongest desirable and significant correlation to the fresh weight of leaves with the DWL/FWL ratio (r = 0.89). Reading the simple regression line equation this correlations, so that each increase by (1 kg/Dunum) fresh weight of leaves will led to an increase in the dry weight of leaves of 0.31 kg/Dunum with a contribution rate of 81%, it is also expected that increasing 1% in the DWL/FWL ratio will led to an increase in the dry weight of leaves of 8.72 kg/ Dunum with a contribution rate of 80%.